THE EVALUATION OF THE QUALITY OF LIFE (QOL) AMONG SENIOR CITIZENS LIVING AT AN OLD AGE HOME ON THE MALAYSIAN EAST COAST - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Ahmad Afif Ahmad Kamari; Nurain Fatini Kamarudin; Nur Athirah Juvono; Nurul Aidasyafikah Mat Arif; Sofya Umairah Zulkarnain (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores the quality of life (QoL) among elderly individuals residing in Malaysian old age homes, focusing on their physical, psychological, and social well-being. It utilizes a quantitative cross-sectional design, employing the Older People’s Quality of Life Questionnaire (OPQOL-35) to assess QoL across multiple domains. The sample comprises 20 participants from Pusat Jagaan Pesakit Dan Warga Emas Seri Damai, aged between 50 and 79, with various age-related health issues. The study’s results indicate no significant gender-based differences in overall well-being. However, females reported lower health scores compared to males. Longer durations of care were associated with lower health quality. Positive correlations were found between overall life satisfaction and factors such as neighbourhood quality, psychological well-being, independence, and engagement in activities. Additionally, health status correlated positively with independence and financial status but negatively with the duration of care. A surprising negative correlation emerged between educational status and social relationships, suggesting that higher education does not necessarily enhance social skills and connections. The discussion highlights the importance of a conducive living environment, the role of psychological well-being in life satisfaction, and the gender disparity in health perception. It also examines the paradox of education and social relationships, the significance of independence in well-being, and the impact of home and neighbourhood on psychological health. The study underscores the benefits of an active lifestyle and leisure activities for emotional well-being and challenges the assumption that extended residency in care centres leads to financial strain. In conclusion, the research emphasizes the need for comprehensive care strategies that consider the diverse needs of the elderly, recognizing the multifaceted nature of their well-being. While limited by its small sample size and cross-sectional design, the study offers valuable insights for improving eldercare practices and informs policymakers and caregivers about the factors influencing elderly well-being. Further research with larger samples is recommended for a deeper understanding of these dynamics.